Impact of open and closed-skill sports on inhibitory control: evidence from event related potentials. - Jiang, Yong; Wu, Yongliang; Zou, Fangyuan; Li, Weijun (International Journal of Sport & Exercise Psychology, 2026)
Inhibitory control can eliminate irrelevant distractions and improve work efficiency, therefore playing a significant role in daily life. A series of studies have confirmed the benefits of exercise in enhancing inhibitory control abilities; however, no research has yet examined the effects of different types of sports on the subfunctions of inhibitory control and their underlying neural mechanisms. This study recruited national-level athletes with open and closed skills, as well as non-athletes, and utilised Go/No Go (to examine response inhibition) and Stroop tasks (to examine interference control), combined with behavioural measures and event-related potentials (ERP) techniques, to investigate the impact of sport types on the cognitive neural processes of inhibitory control. The results revealed that, in terms of behavioural measures, athletes with open skills showed significantly faster reaction times in the Go condition compared to non-athletes. Moreover, they also showed significantly faster reaction times in both the congruent and incongruent conditions of the Stroop task compared to non-athletes. EEG results indicated that in the Go/No Go task athletes with open skills exhibited significantly larger P3 amplitudes compared to athletes with closed skills and non-athletes, suggesting that athletes with open skills have stronger motor inhibition abilities. In the Stroop task, athletes with open skills showed significantly lower N450 amplitudes compared to non-athletes, indicating that athletes with open skills possess more efficient conflict monitoring abilities. This study suggests that exercise benefits inhibitory control, but only sports involving open skills effectively enhances inhibitory control abilities.